A Molecular-Line Study of the Interstellar Bullet Engine IRAS05506+2414 - Sahai, Raghvendra (Astrophys J, 2017)
We present interferometric and single-dish molecular line observations of the interstellar bullet-outflow source IRAS05506+2414, whose wide-angle bullet spray is similar to the Orion BN/KL explosive outflow and likely arises from an entirely different mechanism than the classical accretion-disk-driven bipolar flows in young stellar objects. The bullet-outflow source is associated with a large pseudo-disk and three molecular outflows – a high-velocity outflow (HVO), a medium-velocity outflow (MVO), and a slow, extended outflow (SEO). The size (mass) of the pseudo-disk is 10,350 AU×6,400 AU (0.64–0.17M(⊙)); from a model-fit assuming infall and rotation we derive a central stellar mass of 8–19 M(⊙). The HVO (MVO) has an angular size ~ 5180 (~ 3330) AU, and a projected outflow velocity of ~ 140 km s(−1) (~ 30 km s(−1)). The SEO size (outflow speed) is ~ 0.9 pc (~ 6 km s(−1)). The HVO’s axis is aligned with (orthogonal to) that of the SEO (pseudo-disk). The velocity structure of the MVO is unresolved. The scalar momenta in the HVO and SEO are very similar, suggesting that the SEO has resulted from the HVO interacting with ambient cloud material. The bullet spray shares a common axis with the pseudo-disk, and has an age comparable to that of MVO (few hundred years), suggesting that these three structures are intimately linked together. We discuss several models for the outflows in IRAS 05506+2414 (including dynamical decay of a stellar cluster, chance encounter of a runaway star with a dense cloud, and close passage of two protostars), and conclude that 2nd-epoch imaging to derive proper motions of the bullets and nearby stars can help to discriminate between them.